Effect of Hybrid Modification and Type of Compaction on the Cracking Properties of Asphalt Concrete - Abed, Mohammed A.; Abed, Alaa H. (Al-Nahrain Journal for Engineering Sciences, 2020)
This paper focused on evaluating the effect of aggregate gradation and polymer modification on indirect tensile strength (ITS) and the static stiffness for hot asphalt mixtures. In particular, data from ITS tests have been processed to obtain stiffness measurements through the application of Hondros theory. The results showed that fine mixtures had a better tensile strength by 26.3% than the coarse mixtures. The effect of compaction also was examined, the results showed that samples compacted with the Superpave gyratory compactor (SGC) had an enhancement in ITS by 36.58 and 23.1% in comparison with Marshall and roller compactor respectively. Polymer modifiers were used to estimate their effect on tensile strength, adding 4, 6, and 8% of Styrene-Butadiene-Styrene (SBS), which can rise the ITS by 3.2,6.14 and 13.3% of the non-modified asphalt mixture. Furthermore, using 4, 6, and 8 percent of SBS could increase static stiffness by 53.9, 209.6, and 302.4% respectively for roller compacted fine mixes and 58, 220, and 379.3% for SGC compacted mixes. Furthermore, SBS raised the stiffness modulus by 52.3, 188, and 295% for Marshall compacted mixes. Using hybrid modifier can improve the stiffness of the asphalt mixture. However, The results indicate that using 1, 2 and 3% polyvinyl chloride (PVC) can magnify the stiffness of mixtures by 41.2, 199.8% and 262.6 for roller compacted mixtures and 133.4, 212.1 and 354% for SGC compacted mixtures, whereas there is a stringent increasing by 133.4, 189.2 and 354% for Marshall compacted mixes. Otherwise, polymer-modification can decrease the fracturing index for coarse and fine mixtures.